(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Over the recent years, a lot of authors have noticed changes in risk factors of microbial keratitis development as well as in variety of agents inducing them. Soft contact lens wearing has been reported to be the leading risk factor for infectious keratitis. Purpose. To analyze cases of severe infectious inflammations in the cornea which are associated with contact lens wearing. Materials and methods. We followed up 60 patients (64 eyes) with severe infectious corneal inflammations aged 15 to 63 y/o (М=35.3±SD20.3) who used contact lenses to correct myopia and hypermetropia. CLs were used to correct mild myopia in 10 patients; moderate myopia in 27 patients; and high myopia (6.5D – 20.0D) in 20 patients. Three patients used CLs to correct mild hypermetropia. There were deep stromal keratitides in 16 eyes; corneal ulcers in 34 eyes (including with stromal melting and corneal perforation, 14 and 6 eyes, respectively); corneal abscess-complicated ulcers in 4 eyes; anterior endophthalmitis in 10 eyes. The process was bilateral in four patients. CLs had been used for 0.5 to 44 years (М=9.41±SD7.33). Prior to admission to the Filatov Institute, the patients had received community-based care for 1 to 75 days (M= 21.6±SD19.64). Result. Inflammation was managed and the eye as an organ was preserved in 98.5% of cases (63 yes). Evisceration was performed in one eye. Prospects for surgery with optic purpose were preserved in 54 patients (84.3%). Conclusions. CL users should be dispensary observed as well as be informed of possible infection complications when wearing CL and follow CL using and storage regulations. Once complaints appear it is necessary to attend an ophthalmologist. When infection complications are diagnosed, patients should be immediately referred to a specialized medical institution of a higher level.